Degree of cognitive impairment of older adults institutionalized in two homes for the elderly in the metropolitan area of Bucaramanga-Santander, Colombia - Camargo Hernández, Katherine del Consuelo; Laguado Jaimes, Elveny (Universidad y Salud, 2017)
Introduction: Cognitive impairment is one of the most frequent occurring problems in the older adult population as a result of ageing. Objective: To determine the degree of cognitive impairment of older adults institutionalized in two homes for the elderly in the metropolitan area of Bucaramanga, Santander in Colombia. Materials and methods: A quantitative study was made by using a cross-sectional descriptive design with a population of 165 and a sample of 60 older adults from two homes for the elderly, whose inclusion criteria were: age between 65 to 95 or more and presence or absence of chronic pathology. A non-probabilistic sampling was used for convenience, and the instrument MMSE (Mini-Mental cognitive exam) was applied. Results: The older adult population who participated in the study is between the ages of 75 to 94. Most of them were male, had a primary school level, had family contact and the time for institutionalization was 1 to 5 years. Conclusions: 41.7% of older adults studied showed severe cognitive impairment and require nursing interventions focused on cognitive therapy.